73 Computed Tomography Imaging to Determine Reduction in Intracrainal Pressure Before & After Posterior Vault Expansion in Apert Syndrome. (28th February 2022) - Khera, B.; van de Lande, L.; Sidpra, J.; Knoops, P.; Borghi, A.; Ong, J.; James, G.; Hayward, R.; Schievano, S.; Mankad, K.; Dunaway, D.; Jeelani, N.u.O.; et al.
Abstract: Introduction: Apert syndrome is an autosomal dominant malformation syndrome, accounting for 4.5% of all craniosynostoses. Raised intracranial pressure (ICP) in Apert syndrome has a multifactorial aetiology, with an incidence of up to 45% if left untreated [1, 2]. Raised ICP can be determined clinically, with non-invasive and invasive methods. In this study, we want to assess whether the use of CT scans is reliable in identifying changes in ICP. Method: Pre and postoperative CT scans for 13 Apert syndrome patients who had posterior vault expansion were assessed and graded for severity of intracranial pressure (ICP). The grading system used was departmental specific and the assessment was carried out by a single clinician on different brain structures. This process was repeated on the same patients, using the same CT scans, 4 months later to determine consistency and repeatability. The relationship between the pre and postoperative scans was explored using the chi squared test. Intra-observer variability was assessed using Kappa statistics [SS1]. Results: There was no statistically significant difference between the pre and postoperative CT scan grading. Across instances, only one assessed structure had a p-value <0.05. The Kappa interobserver reliability test did not identify a strong agreement in the comparison of the two instances of data analysis. Conclusions: Assessment of CT scans is not a reliable method to determine changes in intracranial pressure in Apert syndrome patients who have had a posterior vault expansion.